Sensory Reweighting During Bipedal Quiet Standing in Adolescents - Pardo, Alberto; Bermejo, José L; Gandía, Sergio; Maitre, Julien; Villarrasa-Sapiña, Israel; Estevan, Isaac; García-Massó, Xavier (Motor Control, 2021)
A cross-sectional, prospective, between-subjects design was used in this study to establish the differences in sensory reweighting of postural control among different ages during adolescence. A total of 153 adolescents (five age groups; 13-17 years old) performed bipedal standing in three sensory conditions (i.e., with visual restriction, vestibular disturbance, and proprioceptive disturbance). Center of pressure displacement signals were measured in mediolateral and anteroposterior directions to characterize reweighting in the sensory system in static postural control when sensory information is disturbed or restricted during adolescent growth. The results indicate a development of postural control, showing large differences between subjects of 13-14 years old and older adolescents. A critical change was found in sensory reweighting during bipedal stance with disturbance of proprioceptive information at 15 years old. Adolescents of 13-14 years old showed less postural control and performance than older adolescents during the disturbance of proprioceptive information. Moreover, the results demonstrated that the visual system achieves its development around 15-16 years old. In conclusion, this research suggests that a difference of sensory reweighting under this type of sensorial condition and sensory reweight systems would seem to achieve stabilization at the age of 15.
Keywords: adolescence; motor learning; postural stability; sensory disturbance; WOS(2); Scopus